MENGOPTIMALKAN KOMPETENSI GURU YANG BERLATAR BELAKANG PENDIDIKAN UMUM DALAM MEMAHAMI ANAK BERKEBUTUHAN KHUSUS - Sugihartatik Sugihartatik (Education Journal : Journal Educational Research and Development, 2017)
Competence is defined as the knowledge, skills and basic values reflected in the habit of thinking and acting with the knowledge, skills and attitudes of a Master, because a Master must be able to act as a designer, And evaluator (evaluator) learning activities. Competence possessed by a teacher is very useful for peseta learners, especially learners who experience the physical barriers, intellectual, social interaction and communication that we call the child with special needs. On the field, however, it was found that teachers who work at Kebonsari 05 Inclusive School are some of the teachers who do not have the competence to have the skills needed to provide stimulation and motivation to the development of all learners, especially the students who are included in the children with pecial needs.